2017
DOI: 10.1021/acs.macromol.7b01350
|View full text |Cite
|
Sign up to set email alerts
|

ATRP of Methacrylic Derivative of Camptothecin Initiated with PLA toward Three-Arm Star Block Copolymer Conjugates with Favorable Drug Release

Abstract: Three-arm polylactides (PLA) containing 0.2, 7.6, and 13% of d-lactic acid monomeric units were obtained and refunctionalized into ATRP macroinitiators via esterification of hydroxyl groups with 2-bromoisobutyryl bromide. These polymeric matrices underwent enzymatic degradation with various rates and revealed negative results on cytotoxicity and genotoxicity tests. Camptothecin (CPT), which is an anticancer active substance, was transformed into acrylic monomers; however, simple CPT acrylate was not able to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Our results highlight the specific character of the i BuPOSSMA monomer whose behavior can serve as an important model for similar systems incorporating sterically demanding groups in the methacrylate side chain and for monomers with low ceiling temperature in general. For instance, Plichta et al have recently recognized the depropagation‐related effects in polymerization of bulky methacrylate‐based macromonomers aimed at drug delivery applications …”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the specific character of the i BuPOSSMA monomer whose behavior can serve as an important model for similar systems incorporating sterically demanding groups in the methacrylate side chain and for monomers with low ceiling temperature in general. For instance, Plichta et al have recently recognized the depropagation‐related effects in polymerization of bulky methacrylate‐based macromonomers aimed at drug delivery applications …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it can enhance films properties, such as adhesion 156 . Vacuum‐drying is usually utilized for drying PLA films at room or slightly elevated temperature 120,122,123,125,156–161 . For instance, PLA‐based films with plasticizers polyethene glycol and tributyl citrate were prepared by solvent casting method and vacuum drying at 50°C for 4 h to obtain coating material for controlled release of fertilizer in agriculture 162 …”
Section: Methods For Pla Processingmentioning
confidence: 99%
“…Functional properties of PLA materials can be further improved by development of ternary blends 8,22,57,58,60,63,66,67,77,124,159,167 . Klinkajorn & Tanrattanakul 62 added maleic anhydride (0.3–0.6 wt%) to blend of PLA 3 and rubber and improved material mechanical properties (tensile strength from 8 to 24 MPa).…”
Section: Effect Of Process Variables On Pla‐based Materialsmentioning
confidence: 99%
“… 53,60,68,76,77,99,103–110 The ability of such structures to encapsulate hydrophobic drugs, along with the degradable character of the polymers, make these polymers highly valuable for drug delivery 111 . In fact, this is the most investigated biomedical application for star BCPs prepared by combination of ROP and ATRP, with several examples describing the encapsulation of hydrophobic molecules, such as doxorubicin (DOX) or paclitaxel (PTX), or even genetic material by different core‐shell systems for anticancer therapy 112–121 . For example, Li and co‐workers synthesized 3‐ and 6‐arm PCL‐ b ‐PHEMA (PHEMA: Poly(hydroxyethyl methacrylate)) star BCPs by “core‐first,” starting with the ROP of CL followed by the ATRP of HEMA, as effective carriers for PTX delivery 113 .…”
Section: Degradable Star Bcps For Drug Deliverymentioning
confidence: 99%
“…111 In fact, this is the most investigated biomedical application for star BCPs prepared by combination of ROP and ATRP, with several examples describing the encapsulation of hydrophobic molecules, such as doxorubicin (DOX) or paclitaxel (PTX), or even genetic material by different core-shell systems for anticancer therapy. [112][113][114][115][116][117][118][119][120][121] For example, Li and co-workers synthesized 3-and 6-arm PCL-b-PHEMA (PHEMA: Poly(hydroxyethyl methacrylate)) star BCPs by "core-first," starting with the ROP of CL followed by the ATRP of HEMA, as effective carriers for PTX delivery. 113 Results showed that drug loading and drug encapsulation efficiencies of the micelles formed in aqueous medium were influenced by both the number of arms and composition of the stars.…”
Section: Degradable Star Bcps For Drug Deliverymentioning
confidence: 99%